MILITARY GEOGRAPHY: FROM PEACE TO WAR/E.J. PALKA & F.A. GALGANO - Smit, H.A.P. (Scientia Militaria - South African Journal of Military Studies, 2011)
There has always been a long-standing relationship between Geography and the military. In the book Military Geography: from Peace to War, Military Geography is defined as the “application of geographic information, tools and techniques to military problems”. In the international arena, Military Geography enjoys recognition as a formal sub-discipline with its own speciality group within the Association of American Geographers. Military Geography: from Peace to War is a welcome addition to a rather sparse literature collection of this applied sub-discipline of Geography. The book starts with an explanation of the scope of Military Geography that is extremely useful for researchers and students of Military Geography. This explanation enables one to identify the context of the operation under discussion (peacetime, stability and support operations [SASO], or war), the scale of the operation (strategic, operational or tactical), the approach used to study it (systematic, topical or regional) and the perspective of the study (applied and/or historical).